Effects of landscape restoration on migration of lead and cadmium at an abandoned mine site - Zhang, Feiying; Li, Hepeng (Frontiers in Environmental Science, 2022)
Abandoned lead and zinc (Pb/Zn) mining wastes represent a serious environmental hazard because heavy metals (e.g. Pb and Cd) are continuously released into the environment, threatening ecological and human health. This study was devoted to investigate the stability of Pb and Cd in the soil at an abandoned Pb/Zn mine site after landscape restoration by five year monitoring. Chemical extraction was applied to measure the distribution of metals. The results showed that the bioavailability of Pb and Cd in soil increased, during the accumulation of soil organic matter of about 7 g/kg, and the soil pH value decreased from 4.82 to 4.44. Soil organic matter and soil pH significantly affected the distribution of metals. Long-term afforestation can lead to continuous soil acidification. There was a significant negative correlation between the carbonate bound state distribution and soil pH. With the decrease in pH, the decomposition of carbonates was promoted, and relative abundances of Pb and Cd in the distribution associated with fulvic and humic complex of organic matter increased 0.54% and 3.17%, respectively. Pb and Cd showed different migration behavior in pine. Compared with Cd, Pb was more concentrated in roots. These results have important implications for long-term sustainable management of forest formed by phytostabilization of contaminated soil.